UZBEKISTAN POPULATION LABOR OF ACTIVITY STATISTICS ANALYSIS – POPULATION AGE, GENDER, MARITAL STATUS LEVEL - Khudoyberdiev U; Abdurakhmonova Mashhura; Shodikulova Aziza (Bright Mind Publishing, 2025)
This in the article Uzbekistan population labor activity statistics analysis Research population age , gender and education level according to work with employment level to determine The article is focused on labor resources demographic composition , various young groups and sexual categories according to work with employment level , as well as education level and work with employment between dependencies analysis Article results labor market development , worker strength effective distribution and political decisions acceptance in doing important source as service does.
Keywords: Uzbekistan, labor activity, work with employment, age composition, gender, education level, statistics analysis, birth, death, average young.